A Rare Case of Dermatofibrosarcoma Protuberans of the Left Arm - Khushbu Vaidya; Raju Shinde; Sangita Jogdand; Venketesh Rawale; Tushar Nagtode (Journal of Clinical and Diagnostic Research, 2025)
Dermatofibrosarcoma protuberans is a rare form of soft-tissue tumour mostly arising from the dermis layer of the skin, precisely from fibroblastic cells. These are slow growing tumours, usually infiltrating surrounding tissues and are locally invasive. These tumours can infiltrate the subcutaneous tissue, and also the underlying fascia, muscle or deeper structures. These tumours can be neglected due to its initial non-specific and painless clinical presentation. Haemorrhagic and cystic presentations are commonly noticed in large tumours of >5 cm size. It can be classified as low- to intermediate-grade tumours. These are associated with chromosomal translocation, which produces fused COL1A1-PDGFB protein in majority of the cases. Also, dermatofibrosarcoma protuberans has been reported to have higher local recurrences but a favourable prognosis. A regular follow-up is crucial, attributed to its local recurrence risk. These tumours are managed by local incision and adjunct radiation or immunotherapy, if required. This case of 35-year-old male, presented with ulcerative growth over his left arm. The patient was managed by wide local excision and Latissimus Dorsi (LD) flap graft.